Urological surgery in elderly patients: results and complications - Brodak M (Dove Medical Press, 2015)
Milos Brodak, Jan Tomasek, Jaroslav Pacovsky, Lukas Holub, Petr Husek Department of Urology, University Hospital Hradec Kralove, Hradec Kralove, Czech Republic Purpose: Owing to the large aging population, a growing number of elderly patients are undergoing surgical treatment. Surgical procedures in elderly patients are associated with a higher risk of complications. The aim of this study was to evaluate the efficacy and safety of urological surgeries in old patients.Methods: The authors carried out a retrospective study, evaluating results and early postoperative complications in patients aged 75 years and older. The cohort of patients included 221 patients who underwent surgical procedures in the department of urology between January 2011 and December 2012. The average age of patients was 78. The results and complications were categorized based on the type of surgery performed, and the Dindo–Clavien scale.Results: The median follow-up was 18 months. All surgeries for malignant tumors were performed successfully with no residual disease. Totally, 48 (22%) complications were recorded. The most serious were as follows: one patient (<0.5%) died; and four (<2%) patients underwent reoperation. The most common complications involved infection, mainly sepsis and surgical site infections. Other complications included mild respiratory insufficiency, delirium, bleeding, etc.Conclusion: Surgeries in elderly patients were effective and safe. The cornerstone of safety is careful preparation and treatment of comorbidities. Complications occurred mainly as a result of emergency procedures during emergency procedures and in major surgeries such as cystectomy and nephrectomy. The standard use of low molecular-weight heparin caused no incidence of thromboembolic disease. Keywords: urinary tract, aged, postoperative complications, Dindo–Clavien classification